2023
DOI: 10.1186/s12905-023-02169-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of teenage pregnancy and its associated factors in high fertility sub-Saharan Africa countries: a multilevel analysis

Abstract: Background Teenage pregnancies are persistently high among adolescent women in high fertility countries in sub-Saharan Africa. It has been attributed to the high unmet need for family planning in this population. The aim of this study was to determine the prevalence and factors associated with teenage pregnancy in high fertility countries in sub-Saharan Africa. Methods Data for this study was obtained from the most recent Demographic and Health Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 39 publications
3
10
1
Order By: Relevance
“…The reported magnitude of teenage pregnancy in the current study was consistent with other studies conducted in Congo (44.3%) 25 and Niger (40%). 5 The high magnitude of teenage pregnancy in Somaliland is also supported by the report of World Health Organization (WHO) that showed over 90% of teenage pregnancies occur in low-and middleincome countries (LMICs). 26 The possible explanation for it might be due to sociocultural and religious outlooks on the practice of child marriage in the country 27 and also might be due to very low uptake of contraceptive methods.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The reported magnitude of teenage pregnancy in the current study was consistent with other studies conducted in Congo (44.3%) 25 and Niger (40%). 5 The high magnitude of teenage pregnancy in Somaliland is also supported by the report of World Health Organization (WHO) that showed over 90% of teenage pregnancies occur in low-and middleincome countries (LMICs). 26 The possible explanation for it might be due to sociocultural and religious outlooks on the practice of child marriage in the country 27 and also might be due to very low uptake of contraceptive methods.…”
Section: Discussionmentioning
confidence: 90%
“…1 Although declines have observed in all regions, Sub-Saharan African regions continue to have the highest global burden. 4,5 Among them, East Africa has the greatest share with a prevalence of 54.6%. 2 As different studies showed, there are many sociodemographic factors contributing to teenage pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Preventing pregnancy among teenagers and pregnancy-related morbidity and mortality are basic to achieving positive health outcomes across the life course and vital for achieving the sustainable development goals related to maternal and newborn health [ 22 ]. Previous studies conducted elsewhere showed that the prevalence of teenage pregnancy was 44.3% in sub-Saharan Africa [ 23 ], 24.88% in sub-Saharan Africa high fertility countries [ 24 ], 13.42% in the Gambia [ 25 ], and 54.6% in East Africa [ 26 ]. Studies also showed that age, contraceptive utilization, family size, knowledge about contraceptives, marital status, age at first marriage, working status, household wealth status, community-level contraceptive utilization, residence, media exposure, unmet need for family planning, educational level, feelings about the current pregnancy, and relation to the household head were significantly associated with teenage pregnancy [ 23 – 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…7,22 However, it remains the highest in the SSA region. [23][24][25][26] Although ART has had a positive influence on the quality of life among WLWH in Zambia, 27,28 reproductive assistance among these women remains critical to improve child bearing decisions. In resource-constrained settings, identifying factors that influence fertility intentions among WLWH is important for developing strategies and steering appropriate prevention policies that enhance service delivery and reproductive health among this population.…”
Section: Introductionmentioning
confidence: 99%